Gender Differences in Academic Rank in Australian Universities - Austen, Siobhan (National Institute of Labour Studies Inc, 2004)
This study uses information on staff and student characteristics at Australian universities to examine the determinants of the career outcomes recorded for male and female academic staff in 2003. A comparison is also made with data compiled for 2002. Significant differences exist between male and female academics in the probability that they will be employed in one of the top two academic grades. These differences persist even after account is taken of gender-based differences in age, qualifications, discipline area and institution characteristics. The paper discusses these results in the light of human capital theory and alternative economic models of gender-based differences in employment outcomes. Several suggestions are made about future research on gender equity in the university sector.